İDİYOPATİK ANİ İŞİTME KAYIPLARINDA SERUM ANTİ-ISI ŞOK PROTEİN-70 VE PARAOKSONAZ DÜZEYLERİNİN PROGNOZLA OLAN İLİŞKİSİ - DÜZER, SERTAÇ (Fırat Üniveristesi, 2009)
Ani işitme kaybının etyopatogenezi yapılan birçok araştırmaya rağmen net olarak ortaya konmamıştır. Çalışmamızda amaç idiyopatik ani işitme kayıplı hastalarda anti-ısı şok protein 70 (anti-HSP 70) ve paraoksonaz (PON) düzeyleri ile işitme seviyesindeki düzelme arasındaki ilişki ve böylelikle prognozu tahmin etmede bu düzeylerin markır olarak kullanılıp kullanılamayacağını araştırmaktır.Bu çalışma Fırat Üniversitesi Tıp Fakültesi Kulak Burun Boğaz Anabilim Dalı'nda, idiyopatik ani işitme kaybı (İAİK) tanısı alan 25 hasta ve benzer demografik verilere sahip 25 sağlıklı kontrol grubu üzerinde yapıldı. Çalışma grubunu oluşturan hastalardan tedaviye başlanmadan önce ve tedavinin onuncu gününde kan alındı. Kontrol grubundan bir kez alınan periferik kanlar santrifuj edilerek ayrıştırılan serum örnekleri -80°C'de muhafaza edildi. Hastalığı tanımlamak için saf ses odyometrilerinde 250 Hz, 500 Hz, 1000 Hz, 2000 Hz, 4000 Hz, 6000 Hz frekanslardaki işitme kayıpları göz önüne alındı. Tedavinin başlangıcından 10 gün sonra işitmedeki düzelme değerlendirilerek, Siegel sınıflandırmasına göre gruplandırıldıİAİK'lı bireylerin tedavi öncesi PON ve anti-HSP 70 düzeyleri, kontrol grubuyla karşılaştırıldığında PON düzeyleri çalışma grubunda istatistiksel olarak anlamlı derecede yüksek saptandı. Anti-HSP 70 düzeylerinde de kontrol grubuna göre yükseklik saptandı. Ancak istatistiksel olarak anlamlı fark yoktu.Çalışma grubunu oluşturan İAİK'lı bireylerin tedavi öncesi PON düzeyleri ile tedavi bitimindeki PON değerleri karşılaştırıldığında iyileşenlerde yüksek olan PON değerinin daha da yükseldiği, iyileşmeyen olgularda ise daha az yüksek olan PON değerinin düştüğü görüldü. Ancak bu değişimler istatistiksel olarak anlamlı değildi. İAİK'lı olguların tedavi öncesi anti-HSP 70 düzeyleri ile tedavi bitimindeki anti-HSP 70 düzeyleri karşılaştırıldığında, iyileşme görülen hastalarda yüksek olan anti-HSP 70 düzeylerinde istatistiksel anlamlılıkta düşme olduğu, iyileşme görülmeyen hastalarımızda ise belirgin yüksek olmayan anti-HSP 70 düzeylerinde belirgin düşme olmadığı saptandı.Sonuç olarak, İAİK'lı hastaların prognozlarının belirlenmesi ve takiplerinde serum anti-HSP 70 ve PON düzeylerinin markır olabileceğini düşünmekteyiz.Anahtar kelimeler: Ani işitme kaybı, Anti-ısı şok protein 70, Paraoksonaz, Prognoz

Although a lot of researches were fulfilled, the etiopathogenesis of sudden hearing loss wasn?t revealed correctly. The general purpose of our study is, to research the relation between the levels of anti- heat shock protein 70 (anti-HSP 70) and paraoxonase ( PON), and the improvement of the hearing levels by patients with idiopathic sudden hearing losses, and thus researching whether these para meters will be applied as a marker or not in estimating the prognosis.This research was done on 25 patients with idiopathic sudden hearing loss diagnosis, and a healthy control group with relative demographic data of 25 persons of the Fırat University, Medical Faculty, Ear, Nose and Throat (ENT) Department. Blood was drawn from the patients who formed the study group before the treatment started, and on the tenth day of the treatment. Serum samples were centrifuged from the peripheral blood which was drawn once from the control group, and they were stored under -80 °?C. Hear losses of 250 Hz, 500 Hz, 1000 Hz, 2000 Hz, 4000 Hz, 6000 Hz frequencies in the raw voice audiometers were considered to define the disease. An improvement in hearing was measured 10 days after the start of the treatment, and it was arranged in accordance with the Siegel classification.The PON and anti- HSP 70 levels of patients with idiopathic sudden hearing loss were compared with those of the control group, it was determined that the PON levels of the patient group had signifantly high statistics. The Anti-HSP 70 levels were also significantly high in accordance with the control group. However, statistically there was no significant difference.It was observed in a comparison of PON levels before the treatment and at the end of the treatment of patients with idiopathic sudden hearing loss who constitute the study group that, the PON level had increased of recovering patients with idiopathic sudden hearing loss who already had a high PON level, and that the PON level had decreased of patients with idiopathic sudden hearing loss who didn?t show any improvement, and who had a lower PON level. However, these changes weren?t statistically significant. It was observed in a comparison of anti-HSP 70 levels before the treatment and at the end of the treatment of patients with idiopathic sudden hearing loss who constitute the study group that, there was no decrease in the anti-HSP 70 level of recovering patients with idiopathic sudden hearing loss who already had a high anti-HSP 70 level, and that there was no significant decrease in anti-HSP 70 level of patients with idiopathic sudden hearing loss who didn?t show any improvement, and who didn?t have a significant anti-HSP 70 level.Finally, we assume that, serum anti-HSP 70 and PON levels can be markers in determining and monitoring prognosis of patients with idiopathic sudden hearing loss.Key words: Sudden hearing loss, anti-HSP 70, Paraoxonase, Prognosis.
The relationship between the serum levels of hsp-70 and pon with the prognosis in the sudden sensorineural hearing loss.
Keywords: Kulak Burun ve Boğaz